The dissociation mechanism and thermodynamic properties of HCl(aq) in hydrothermal fluids (to 700 °C, 60 kbar) by ab initio molecular dynamics simulations - Mei, Y.; Liu, W.; Brugger, J.; Sherman, D.; Gale, Julian (Pergamon, 2018)
HCl is one of the most significant volatiles in the Earth’s crust. It is well established that chloride activity and acidity (pH) play important roles in controlling the solubility of metals in aqueous hydrothermal fluids. Thus, quantifying the dissociation of HCl in aqueous solutions over a wide range of temperature and pressure is crucial for the understanding and numerical modeling of element mobility in hydrothermal fluids. Here we have conducted ab initio molecular dynamics (MD) simulations to investigate the mechanism of HCl(aq) dissociation and to calculate the thermodynamic properties for the dissociation reaction at 25–700 °C, 1 bar to 60 kbar, i.e. including high temperature and pressure conditions that are geologically important, but difficult to investigate via experiments.